(untitled) (International Seven Journal of Multidisciplinary, 2026)
Colorectal cancer (CRC) is the third leading cause of malignant neoplasia and the second leading cause of global cancer mortality (Sun et al., 2024). Due to the epidemiological aspects of this neoplasm, being more prevalent at older ages, this article focuses on this population group. Considering the physiological and pathological changes of aging (senescence and frailty), the elderly population has gained prominence in the search for better methods to ensure earlier diagnosis, improved screening strategies, and innovative targeted therapies that provide greater tolerability for this age group during oncological treatment. It is known that this group is more vulnerable and presents a higher prevalence of comorbidities compared to others. This study aims to conduct a review of current evidence on improvements in diagnostic protocols, such as the incorporation of proteomic analysis combined with non-genetic and genetic risk factors (Elez et al., 2025), and in oncological targeted therapies, such as cetuximab, bevacizumab, and FOLFOX for CRCs with KRAS mCR and BRAF mutations (H. Ahn et al., 2024; Elez et al., 2025). The analysis of the results shows that when individualized beyond chronological age, there is a positive association between research and techno-pharmacological innovation, targeted therapies focusing on oncopathogenesis, new diagnostic predictors, and improvement in prognostic indicators for the studied population.